(untitled) (Research, Society and Development, 2022)
Burnout syndrome is a psychological syndrome resulting from a continuous response to chronic interpersonal stressors during work. The emergency department is a place of stress and multidisciplinary work, with situations linked to a vital risk for patients in many cases. The present study aims to describe the factors that lead to the development of Burnout Syndrome in health professionals in emergency services. This is a study with a qualitative approach, where an integrative literature review was adopted. Performed through the Virtual Health Library (BVS) in Pubmed databases, using the crossings of the English descriptors “Burnout syndrome”, “Risk factors”. For the evaluation of the research problem and its stratification, the PVO strategy was used. The emergency service accumulates many characteristics of a stressful job: heavy workload, emergency work, zapping, “always more and always better” with constant resources, uncertainty, lack of recognition and frustration, interpersonal conflicts, just-in-time production , from incivility to environmental violence. A possible explanation for this fact could be the emergency routine, considering that the professional is dealing directly with life-threatening situations and that there is an overload of shifts. PS professionals are a vulnerable group, as nearly half of them experience burnout. Indeed, they are faced with intense and repetitive situations typical of the emergency profession that constitute a favorable terrain for the development of stress and burnout.